miR-17 acts as a tumor suppressor by negatively regulating the miR-17-92 cluster - Yan Sweat; Ryan J. Ries; Mason Sweat; Dan Su; Fan Shao; Steven Eliason; Brad A. Amendt (Elsevier, 2021)
Anaplastic thyroid cancer (ATC) is an aggressive, highly metastatic cancer that expresses high levels of the microRNA (miR)-17-92 cluster. We employ an miR inhibitor system to study the function of the different miRs within the miR-17-92 cluster based on seed sequence homology in the ATC SW579 cell line. While three of the four miR-17-92 families were oncogenic, we uncovered a novel role for miR-17 as a tumor suppressor in vitro and in vivo. Surprisingly, miR-17 inhibition increased expression of the miR-17-92 cluster and significantly increased the levels of the miR-18a and miR-19a mature miRs. miR-17 inhibition increased expression of the cell cycle activator CCND2, associated with increased cell proliferation and tumor growth in transplanted SW579 cells in xenograft mice. miR-17 regulates MYCN and c-MYC expression in SW579 cells, and the inhibition of miR-17 increased MYCN and c-MYC expression, which increased pri-miR-17-92 transcripts. Thus, inhibition of miR-17 activated the expression of the oncogenic miRs, miR-18a and miR-19a. While many cancers express high levels of miR-17, linking it with tumorigenesis, we demonstrate that miR-17 inhibition does not inhibit thyroid tumor growth in SW579 and MDA-T32 ATC cells but increases expression of the other miR-17-92 family members and genes to induce cancer progression.